Waiting Time for Pharmaceutical Installation Services on Outpatients Using Electronic Medical Records at RUMKIT TK II Udayana Denpasar Bali - Sejati, Ambarwati Wardoyo; Wardani, Silvia Intan; Noviyanti, Ni Putu Ayu Wulan (Poltekkes Kemenkes Semarang, 2024)
The waiting time for pharmaceutical services is an important indicator in assessing the quality of health services, including at Tk II Udayana Hospital, Denpasar Bali. Although the implementation of Electronic Medical Records (RME) has been implemented to improve efficiency, outpatients still often face quite long wait times. This study aims to analyze factors such as prescription type, destination poly, gender, and visit time that affect the waiting time of pharmaceutical services at the hospital's Pharmacy Installation. This study uses an observational analytical approach with a cross-sectional design, involving 205 outpatient data taken by Simple Random Sampling in June 2024. The collected data was then analyzed using the Chi-Square test to determine the relationship between independent and dependent variables. The results of the analysis showed that the type of prescription had a significant relationship with the waiting time for pharmaceutical services (p=0.001). Patients who received a concocted prescription experienced a longer wait time than patients who received a non-concocted prescription. However, other variables such as gender (p=0.099), visit time (p=0.091), and destination poly (p=0.084) did not show a significant relationship with waiting time. From the results of the study, the type of prescription proved to be the most influential factor on the waiting time for pharmaceutical services at Tk II Udayana Hospital. Therefore, efforts are needed to optimize the RME system and improve resource management, especially in handling concocted prescriptions, to reduce waiting times and increase patient satisfaction.